2022
DOI: 10.1177/10732748221081369
|View full text |Cite
|
Sign up to set email alerts
|

Period 2 Suppresses the Malignant Cellular Behaviors of Colorectal Cancer Through the Epithelial-Mesenchymal Transformation Process

Abstract: Introduction The PER2 (Period circadian regulator 2) gene is related to the circadian clock, and it has been deemed as a suppressor gene in osteosarcoma and lung carcinoma. However, the part of PER2 in CRC (colorectal cancer) needs to be further determined. Methods First, we collected clinical samples to detect PER2 expression in CRC. Then, we used cell transfection to knock down PER2 expression in CRC cell lines and performed a series of functional experiments to elucidate the effects of PER2 on CRC cells. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
(70 reference statements)
0
10
1
Order By: Relevance
“…Mostafaie et al ( 40 ) demonstrated a correlated decrease in Per1 and estrogen receptor-β in colorectal tumours. Furthermore, six studies reported that Per2 expression was significantly decreased in tumour tissues ( 39 , 48 - 52 ). Hasakova et al ( 50 , 53 ) found that Per2 was downregulated in tumour tissues of male patients with CRC, but Krugluger et al ( 45 ) determined that Per2 expression exhibited no differences in colon tumour tissues; the following six studies also confirmed this ( 38 , 40 - 42 , 47 ).…”
Section: Associations Between Crc and Circadian Clock Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostafaie et al ( 40 ) demonstrated a correlated decrease in Per1 and estrogen receptor-β in colorectal tumours. Furthermore, six studies reported that Per2 expression was significantly decreased in tumour tissues ( 39 , 48 - 52 ). Hasakova et al ( 50 , 53 ) found that Per2 was downregulated in tumour tissues of male patients with CRC, but Krugluger et al ( 45 ) determined that Per2 expression exhibited no differences in colon tumour tissues; the following six studies also confirmed this ( 38 , 40 - 42 , 47 ).…”
Section: Associations Between Crc and Circadian Clock Genesmentioning
confidence: 99%
“…Healthy mice exhibited rhythmicity of Per1, Per2, Wee1 and p21 in the intestine, but the circadian rhythmicity was significantly reduced in tumours ( 58 ). Knocking down Per2 subsequently inhibited p53 and caused CRC cells to acquire malignant biological features ( 52 ). Studies have explained how periodic genes regulate CRC progression by interfering with the cell cycle.…”
Section: Associations Between Crc and Circadian Clock Genesmentioning
confidence: 99%
“…PER and CRY genes: Studies indicated that the PER gene acted as an anti‐tumour factor, and the CRY gene acted as a cancer‐promoting factor in CRC. Xiong et al reported that the knockdown of PER2 promoted migration by activating the EMT pathway and the Snail/Slug axis by inhibiting p53 [41]. Some studies also demonstrated that the low expression of PER2 was associated with high metastasis and poor prognosis in CRC patients [36, 42].…”
Section: The Effect Of Core Circadian Genes On Crcmentioning
confidence: 99%
“…The knockdown of BMAL1 inhibited metastasis by tipping Cell cycle and proliferation Overexpression inhibits tumour cell proliferation; regulates oxaliplatin-mediated G2-M phase arrest by activating ATM pathway [33] Overexpression prevents tumour cells from entering G1 to S phase via suppression of CyclinD1 expression [34] Metastasis Overexpression induces metastasis by stimulating exosome excretion [37] Knockdown leans epithelial-mesenchymal balance towards epithelial properties [38] Low expression promotes metastasis and shows poor prognosis [36] Stemness of cells Knockdown increases tumour initiation and increases self-renewal of intestinal stem cells by activating Hippo signalling. (Yes-associated protein 1-dependent) [46] Metabolism Disruption leads to metabolic phenotype rewiring via HKDC1, an increase in glycolytic activity, as well as changes in treatment response [35] Knockout drives APC loss of heterozygosity to hyperactivates Wnt singling, which upregulates c-Myc and drives heightened glycolytic metabolism [11] Drug resistance Knockdown decreases the chemoresistance [38] High expression shows poor clinical outcomes following anti-angiogenic drug therapy via decreasing the synthesis of VEGF-A [51,52] Enhances oxaliplatin induced apoptosis [33] CLOCK Cell cycle and proliferation Overexpression prevents tumour cells from entering G1 to S phase via suppression of CyclinD1 expression [34] Overexpression promotes tumour cell proliferation via regulating iron metabolism [39] Metastasis Overexpression promotes the metastasis by enhancing the expression of angiogenesis-related genes (HIF-1α, ARNT and VEGF) and promoting EMT [40] PER1/2/3 Metastasis Knockdown promotes migration by activating EMT pathway and activates the Snail/Slug axis through inhibiting p53 [41] Low expression shows high metastasis and poor prognosis [36,42] Drug resistance Overexpression reduces chemoresistance and self-renewal capability of CRC stemlike cells via inhibition of Notch and β-catenin signalling [47].…”
Section: The Effect Of Core Circadian Genes On Crcmentioning
confidence: 99%
See 1 more Smart Citation